2017
DOI: 10.1111/btp.12521
|View full text |Cite
|
Sign up to set email alerts
|

Logging, exotic plant invasions, and native plant reassembly in a lowland tropical rain forest

Abstract: Habitat modification and biological invasions are key drivers of global environmental change. However, the extent and impact of exotic plant invasions in modified tropical landscapes remain poorly understood. We examined whether logging drives exotic plant invasions and whether their combined influences alter understory plant community composition in lowland rain forests in Borneo. We tested the relationship between understory communities and local‐ and landscape‐scale logging intensity, using leaf area index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
(106 reference statements)
3
16
0
Order By: Relevance
“…As with the species composition analyses, distance to forest edge had no significant effect on the mean functional trait value of forest communities for any trait (Appendix S1). Our study also supported previous findings that closed canopy rainforest have low levels of invasion (Dawson, Burslem, & Hulme, 2015;Döbert et al, 2017a;Teo et al, 2003), and provided the first evidence of this result in conservation set-asides embedded within oil palm plantations. Despite most remnants being small in size (<100 ha; no.…”
Section: Functional Trait Filteringsupporting
confidence: 90%
See 1 more Smart Citation
“…As with the species composition analyses, distance to forest edge had no significant effect on the mean functional trait value of forest communities for any trait (Appendix S1). Our study also supported previous findings that closed canopy rainforest have low levels of invasion (Dawson, Burslem, & Hulme, 2015;Döbert et al, 2017a;Teo et al, 2003), and provided the first evidence of this result in conservation set-asides embedded within oil palm plantations. Despite most remnants being small in size (<100 ha; no.…”
Section: Functional Trait Filteringsupporting
confidence: 90%
“…logging; Broadbent et al., 2008; Laurance et al., 2011; Lôbo, Leão, Melo, Santos, & Tabarelli, 2011). These disturbances result in physical gaps in the canopy, which increase light levels and thus facilitate the establishment of introduced exotic propagules (Döbert, Webber, Sugau, Dickinson, & Didham, 2017a; Peters, 2001; Teo, Tan, Corlett, Wong, & Lum, 2003; Waddell, Banin, et al., 2020). Many exotic species are not well adapted to closed canopy, intact forests, however, and habitat filtering may mean that only a few shade‐tolerant species present in the landscape can establish and persist in these environments (Dawson, Burslem, & Hulme, 2009; Koike, 2001; Martin & Marks, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…high seed number, fast growth rate, early age of reproduction, asexual reproduction, fruits produced year round and very large seed bank), allowing for rapid population growth (Rejmánek and Richardson 1996;Singhakumara et al 2000;Daehler 2003), making it a highly invasive species and a pest throughout most of its introduced range (Wester and Wood 1977;Gerlach 1993). Similar patterns have been observed in temperate forests with dominant invasive species disrupting native seedling growth (Gorchov and Trisel 2003;Stinson et al 2006), and in selectively logged Malaysian tropical rainforests, Döbert et al (2017) found fewer Dipterocarpaceae seedlings where exotic biomass was higher. Therefore, high niche overlap may lead to strong competition between young trees and exotic shrubs for resources such as light.…”
Section: Increased Invasion In Disturbed Forestssupporting
confidence: 80%
“…Voucher specimens and photographs of plants in the quadrats were used to identify individuals by a botanist at Danum Valley Field Centre (co-author BBO) and the herbarium at the Forest Research Centre, Sepilok. Exotic species were identified based on lists and guides of Sabah's known exotic plants prepared prior to fieldwork (see Pallewatta et al 2003;Bakar, 2004;Peh, 2010;Döbert et al 2017;Fee et al 2017;CABI 2017) and confirmed by botanists from vouchers. The observed number of exotic species and number of exotic stems per plot were used as measurements of invasion within a plot.…”
Section: Plot-level Surveys Of Native and Exotic Plantsmentioning
confidence: 99%
See 1 more Smart Citation